Management of Colletotrichum truncatum causing anthracnose/ pod blight of soybean by fungicides - and UTPAL DEY, G.P. JAGTAP*, D.S. GAVATE (Indian Phytopathology, 2013)
A study was conducted during 2009 to 2010 to control Colletotrichum truncatum causing anthracnose/pod blight of soybean with fungicides. All the fungicides evaluated in vitro were found effective against C. truncatum and recorded significant inhibition of the test pathogen over untreated control. However, among the nine fungicides, carbendazim recorded least mean colony diameter (7.52 mm) and highest inhibition (91.63%) of mycelial growth over untreated control, followed by mancozeb which recorded mean colony diameter of 10.38 mm and mean mycelial growth inhibition of 88.45 per cent. In field, carbandazim (@ 0.1%) recorded least mean disease intensity (19.55%), mean pod infection (9.63%), highest seed yield (2605 kg/ha) and test weight (14.33 g). It also recorded highest reductions in the disease intensity (40.73%), pod infection (75.73%) over unsprayed control followed by mancozeb (@ 0.1%) which recorded the minimum mean disease intensity (21.50%) and pod infection (10.78%). Considering incremental cost : benefit ratio (ICBR), the most economical treatment which recorded highest cost : benefit ratio was the fungicide carbendazim (C:B ratio, 1:14.45) followed by Carbendazium + Mancozeb (C:B ratio, 1:8.92).